(untitled) (Journal of Human Sciences, 2021)
Scientific research is one of the most important basic functions of universities and it is an important and vital element in their life as scientific and intellectual institutions, as it is one of the most important measures indicating the leadership role of universities in the scientific and cognitive fields. Rather, the reputation and prestige of universities are largely related to the scientific research they produce and publish. The research presented by students in the last stage of the initial university study aims to train students develop their talents expand their perceptions organize their ideas and express what is on their minds. Hence the importance of research in identifying the most important research problems facing our students in writing graduation research and finding appropriate solutions to it by providing all the needs that help students to complete their research. This study aims to identify the most important obstacles facing the students of the college of education, bani walid university, in preparing their graduation research. And to identify the differences between the average grades of students of the college of education, bani walid university, in the preparation of graduation research according to the gender variable (male-female). And to identify the differences between the averages of students of the college of education, bani walid university, in preparing graduation research according to the variable of specialization, as well as trying to prepare a proposed scenario to help students prepare graduation research. The study population consists of all students of the faculty of education, bani walid university, who have a seminar and a graduation project, and their number is (30) male and female students. The two researchers used the questionnaire as a means of collecting information. The study reached several results, including: the difficulties faced by students in these departments when preparing graduation projects are due to the lack of books and references, as well as the lack of supervisors able to assist them in completing these projects, which usually require a special research environment, and the lack of course development to keep pace with modern technology. On the one hand, the supervisors’ lack of commitment to supervise their students in the required manner according to scientific standards and controls. There are statistically significant differences between male and female students in favor of male students in the type of problems they face in preparing the graduation project.